# Using identities factorise the following: 1. 9y2-66yz+121z2 (after i.e., xyz those are squares not numbers) 2.(x2-1) (x4+x2+1)

2
by tanyataj5

2015-08-25T23:18:01+05:30
1. Using identity

( a - b )² = a² + b² - 2ab,

⇒( 3 y - 11 z ) ² = 9 y ² + 121 z ² - 66 yz
⇒9 y ² + 121 z ² - 66 yz =9 y ² + 121 z ² - 66 yz

L.H.S. = R.H.S

2015-08-26T05:20:43+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
9 y² - 66 y z + 121 z²
= (3y)² - 2 * 3 y * 11 z + 11² z²
= (3 y - 11 z)²

the identity used is    a² - 2 a b + b²  = (a - b)²
=============
x⁴ + x² + 1  = y² + y + 1        if  y = x²

we know that  (a - b) (a² + a b + b²) = a³ - b³
or,  (y - 1) ( y² + 1 * y + 1²) = y³ - 1³

(x² - 1) * (x⁴ + x² + 1)
= (x⁶ - 1)

click on thanks button above